Mental disability management within occupational health surveillance - Buselli, Rodolfo; Del Guerra, Paolo; Caldi, Fabrizio; Veltri, Antonello; Battaglia, Susanna; Baldanzi, Sigrid; Girardi, Michelle; Sallese, Domenico; Dell'Osso, Liliana; Cristaudo, Alfonso (La Medicina del Lavoro, 2020)
Introduction: The management of workers with mental disability is a current topic of great interest. The aim of the article is to report the experience of managing cases of employees with mental disabilities in an Italian university hospital and to describe the preventive measures adopted and the therapeutic programs carried out. Methods: A group of 100 workers suffering from psychiatric disorders has been included in a medical surveillance program lasting at least 6 months. The workers were followed up within a protocol that included psychiatric visits, psychotherapeutic interventions, visits by the occupational physician and medico-legal evaluations. Evaluation scales of disease severity and treatment efficacy (CGI) and overall functioning (GAF) were administered at the baseline and after 6 months of follow-up. Results: The sample was mainly composed of nurses (44%) and nursing assistants (24%) and the most commonly diagnosed disorders were mood and anxiety disorders. Participation in the medical surveillance program with the implementation of specific therapeutic strategies and organizational interventions resulted in a statistically significant reduction in the severity of the disease and an improvement in overall functioning and made it possible to keep the job and place of work in almost all cases. Discussion: The results of this experience allow us to affirm that the integration of skills is a valid tool both for the multidisciplinary diagnostic assessment and for the monitoring and management of workers with mental disability under periodic health surveillance.